Lecturers’ Challenges: Teaching English by Using Blended Learning in Pandemic Era at PGRI Silampari University - Ayu Oktaviani; Yulfi Yulfi; Deva Sugianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research aimed to discover the lecturers' challenges in teaching during the pandemic situation at PGRI Silampari University. The method used in this research was the descriptive qualitative approach. The subjects of this research were five lecturers in the English education study program. In collecting the data, the researcher used two instruments. There were questionnaires and interviews. The researcher followed three concurrent activity flows to analyze the data: data condensation, data display, and conclusion, for the results showed some challenges they faced when implementing teaching and learning activities in blended learning both in the online and offline classroom. The challenges were the lack of student control and monitoring, the problem in applying technology, and the problem with time allocation due to the Pandemic. In conclusion, students faced many challenges in teaching by applying blended learning during Pandemic Covid -19 at PGRI Silampari University. Keywords: blended learning, challenges, lecturer. This research aimed to discover the lecturers' challenges in teaching during the pandemic situation at PGRI Silampari University. The method used in this research was the descriptive qualitative approach. The subjects of this research were five lecturers in the English education study program. In collecting the data, the researcher used two instruments. There were questionnaires and interviews. The researcher followed three concurrent activity flows to analyze the data: data condensation, data display, and conclusion, for the results showed some challenges they faced when implementing teaching and learning activities in blended learning both in the online and offline classroom. The challenges were the lack of student control and monitoring, the problem in applying technology, and the problem with time allocation due to the Pandemic. In conclusion, students faced many challenges in teaching by applying blended learning during Pandemic Covid -19 at PGRI Silampari University. Keywords: blended learning, Challenges, Lecturer.